First records of the subgenus Eurhipidia from Japan, with two new species (Diptera, Limoniidae, Rhipidia ) - Kato, Daichi (Journal of Asia-Pacific entomology, 2024)
Species of Rhipidia (Eurhipidia) Alexander, 1965 are found in Japan for the first time. Two new species, R. (E.) honshuensissp. nov. from Honshu (Palaearctic Region) and R. (E.) okinawensissp. nov. from Nansei Islands (Oriental Region) are described. The images of the habitus, wings, and terminalia, distribution maps, and a key to the species are provided.